IMPACT OF COVID-19 ON UTILIZATION OF DENTAL SERVICES BY PATIENTS VISITING TERTIARY CARE DENTAL CENTRE LAHORE - Akhtar, Qayyum; Mahmood, Khalid; Qayyum, Umer; Rana, Nadeem Ahmed; Sajjad, Hafiza Qurat-Ul-Ain; Naeem, Amjad (Pakistan Armed Forces Medical Journal, 2020)
Objective: To assess the impact of COVID-19 pandemicon utilization of Dental services by patients visiting a tertiary care dental centre in Lahore, Pakistan.Study Design: Cross-sectional comparative study.Place and Duration of Study: 28 Military Dental Centre, Combined Military Hospital Lahore Medical and Dental College, from Feb to Apr 2020.Methodology: There cords of patients reported from 17 February to 16 April 2020 were retrieved from unit’s data bank and analysed. The patients’ demographic data and presenting complaints in pre-COVID group vs COVID group were compared using SPSS version 22.Results: A total of 3173 patients, 1802 Male and 1371 Females reported for routine and emergency dental services. The age ranged between 5 to 79 years (31.97 ± 13.032). 84% (248 vs 2925) less patient visited during COVID compared to Pre-COVID period Significantly less female visited 1337 (45.7%) vs 34 (13.7%) during COVID period (p